2022
DOI: 10.3390/healthcare10030561
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Equine Therapy Intervention on Activities of Daily Living, Quality of Life, Mood, Balance and Gait in Individuals with Parkinson’s Disease

Abstract: Objectives: The objective of this study was to evaluate the efficacy of equine therapy (ET) to detect changes in the activities of daily living, quality of life, mood, balance, and gait in individuals with Parkinson’s disease (PD). Material and Methods: In the study, 17 participants with PD were recruited to participate in 10 sessions of ET. The inclusion criteria of the study were: second and third stages of the Hoehn and Yahr scale, Mini-Mental State Examination (MMSE) greater than or equal to 24 points, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
1
0
2
Order By: Relevance
“…However, studies of people with conditions other than dementia, such as stroke survivors, typically did not recruit based on age or cognitive impairment. Terefore, we considered but had to exclude a small number of studies that did not meet criteria for either age or cognitive impairment, for example, studies of forest walking for poststroke depression and anxiety [65], nature-based rehabilitation for poststroke fatigue, anxiety, and depression [66], and equine therapy for gait, balance, and mood in Parkinson's disease [67,68]. Tis meant that in practice, all the included studies focused on people with dementia, a condition where the presence of cognitive impairment is a given, but a small proportion of people are diagnosed below the age of 65.…”
Section: Limitationsmentioning
confidence: 99%
“…However, studies of people with conditions other than dementia, such as stroke survivors, typically did not recruit based on age or cognitive impairment. Terefore, we considered but had to exclude a small number of studies that did not meet criteria for either age or cognitive impairment, for example, studies of forest walking for poststroke depression and anxiety [65], nature-based rehabilitation for poststroke fatigue, anxiety, and depression [66], and equine therapy for gait, balance, and mood in Parkinson's disease [67,68]. Tis meant that in practice, all the included studies focused on people with dementia, a condition where the presence of cognitive impairment is a given, but a small proportion of people are diagnosed below the age of 65.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition to transdiagnostic benefits, the literature suggests that EASs are associated with a reduction in symptoms associated with specific psychiatric disorders. As stated above, studies of community populations have reported benefits for a variety of psychiatric conditions [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]99,100,142,143], including trauma-related symptoms [66,[104][105][106][107]. Veteranspecific studies have reported an improved effect [51,[56][57][58]109,110], and psychological flexibility [57,58], as well as decreased anxiety [51,56,59,60], depression [46,50,53,[57][58][59][60][61...…”
Section: Transdiagnostic Benefits and Symptom Reductionmentioning
confidence: 99%
“…quantitative Messung der körperlichen Aktivität über Pedometer (Marke Omron) [21,22] 0 T0 In der Literatur finden sich Einzelfallberichte und eine unkontrollierte Single-Center-Studie aus Italien [23] mit mittlerem Evidenzlevel, die unsere Ergebnisse bestätigen.…”
Section: Motorische Testung Psychometrische Testung Erfassung Der Beh...unclassified
“…Messungen mit der Kraftmessplatte erscheinen von untergeordneter Aussagekraft. Dieses Ergebnis steht in Einklang mit den Untersuchungen von Berardi et al [23].…”
Section: Motorische Testung Psychometrische Testung Erfassung Der Beh...unclassified